Percepção e comportamento ambiental de consumidores de produtos orgânicos das feiras do Parque Água Branca - Gonçalves, Kleber Spíndola (2017)
Organic agriculture, unlike conventional agriculture, does not use agrochemicals, hormones, genetically modified seeds, among other things, it offers healthy food, contributing to environmental and social sustainability. Organic agriculture has procedures that start from the preparation of the soil to the commercialization phase of production, thus serving the entire chain of production until commercialization. Initiatives to strengthen organic agriculture such as the creation of organic fairs, such as the Parque Água Branca fair, strengthens the development of the activity. There is a growing and growing market due to the population's concern about health and the increase in cases of diseases related to the use of pesticides in plantations that cause damage to the environment and health of the population. Therefore, the objective was to analyze the perception of consumers of organic products on these foods as well as organic fairs. For this, a quanti-qualitative research was structured through a semi-structured script. It was possible to collect information such as gender, age, schooling, if you have children, neighborhood that resides, attendance at the fair, who usually attends the fair, how to go to the fair, whether to attend other organic fairs in the city, Consuming organic food, which led him to consume organic foods in addition to information on the degree of agreement of the respondent on environmental, health and price factors, as well as information about the respondent's point of view on the organic fair. There were 14 organic fairs in the city of São Paulo. As a study site, the fairs located in Água Branca Park were selected. In all, a total of 360 interviews were held in the four organic fairs held on the site, being the fair from Tuesday morning, Tuesday evening, Saturday and Sunday morning. The research was divided into three stages, where a documentary survey and direct observation about the organic fairs of the city of São Paulo were carried out. In the second stage, the fair was selected for the study. In step three, a script of interviews with open and closed questions was structured to answer the questions of this research. After completing the three steps, the interviews were performed and the data were analyzed using the Statistical Package for the Social Sciences (SPSS) software. It was identified after the analysis that the consumer of organic foods began consumption for health-related aspects, but the concern related to the environment was also reported. He realized that the fair is a place not only to buy organic food, but rather a walk with the family that brings well-being and satisfaction, because it is possible to know and have contact with those who produce the food purchased by the consumer. Benefits related to Água Branca park have also been reported and are directly related to the organic fair. It is perceived a group of consumers concerned about their health, the environment and the relationship between rural producers and consumers.